The Effect of Smoking on the Labor Market - Bryndís Þóra Guðmundsdóttir 1980- (2011)
INTRODUCTION: Cigarette smoking is known to cause many types of cancer, chronic bronchitis, ischemic heart disease and stroke among other diseases. Studies have shown that cigarette smoking can have a negative effect on labor market outcomes, such as wages. The effects of cigarette smoking on employment have not been given much attention and currently available results differ widely. The aim of this study was to examine the relationship between cigarette smoking and changes in employment status after the Icelandic banking collapse in the fall of 2008. METHODS: The data used in this study originates from the health and lifestyle survey “Heilsa og Líðan Íslendinga” carried out by the Public Health Institute of Iceland in the years 2007 and 2009. The sample was a stratified random sample of 9,807 individuals between 18-79 years. The 2009 version of the questionnaire was sent to all those that participated in the 2007 survey. The net-response rate in 2007 was 60.8%. In 2009 the response rate was 69.3%, which correspond to 42.1% of the original sample responded the questionnaires in both 2007 and 2009. Probit analyses were used when examining the relationship between employment status and smoking (in 2007 and 2009). Ordered probit analysis was used when estimating the relationship between income and smoking. RESULTS: The main finding in this study is that there might be a negative relationship between income and being a daily smoker. This negative relationship is statistically significant at traditional levels for males but not for females. The negative relationship is stronger for the 2009 data both for males and females. There were no statistical significant relationships observed at traditional levels for having lost a job and being a daily smoker. For the other labor-market outcome, being employed were the marginal effects positive of being a daily smoker in 2007 compared to non-daily smokers, both for males and females. In contrast were the marginal effects negative in 2009 for daily smokers compared to ...